BRAC donor consortium: Rural Development Programme-phase II and Rural Credit Programme, mid-term evaluation - BRAC (© BRAC, 2016)
1. Introduction 2. Summary recommendations 3. BRAC in context 4. Performance in resource utilization 5. Credit management 6. Operational programmes 7. Support services 8. Socioeconomic effects 9.Management and organizational capacity